Evaluating the perceived impact of an interprofessional childhood obesity course on competencies for collaborative practice. Issue 3 (3rd May 2016) - Iachini, Aidyn L.; Dunn, Brianne L.; Blake, Christine; Blake, Elizabeth W.
ABSTRACT: Interprofessional education (IPE) is needed to prepare health professional students to address the complexities of childhood obesity in practice. This mixed-method study sought to evaluate the perceived impact of a childhood obesity IPE intervention on health professional students' collaborative competency development within two domains: roles/responsibilities and teams/teamwork. Fourteen health professional students participated in this mixed-methods study. Quantitative data were collected through pre/post surveys, while qualitative data were collected through reflection assignments. Survey findings indicated that students reported significant increases in growth within both interprofessional competency domains. Qualitative data elaborated on the types of learning students experienced relative to each domain. Implications of this study for research and practice related to IPE to address complex health issues, such as childhood obesity, are shared.